The Implementation of Project-Based Learning Model Based on Local Food Potency in Developing Entrepreneurship Attitude of Primary School Students - Koban, Gaudensia Hiba Soja; Linuwih, Suharto; Purwanti, Eko (Journal of Primary Education)
This study has a purpose of finding out the effect of implementation of project-based learning, based on effective local food potencies in developing entrepreneurship attitudes of primary school students. The study is a concurrent embedded mix method research which combines quantitative and qualitative in imbalance natures with primary and secondary data. The primary approach in this study is quantitative study, the learning achievement by using the model of project-based learning on local food potencies. The secondary is qualitatively seen from entrepreneurship attitudes of the students. To get the quantitative data, this study went through pre-test and post-test meanwhile the qualitative data was gained through observation, interviews, and documentation. The data gained was analyzed using SPSS 16.0 for Windows and triangulation. Project-based learning model based on local food potencies is effective in developing entrepreneurship attitudes of the students. It is seen from the improving attitudes in each session, first meeting with 69.71, second and third meeting were 76.3 and 84.32. Based on the findings, it can be concluded that the learning model is effective in developing the entrepreneurship attitudes of the students.